THE EFFECT OF USING THE YOUTUBE APPLICATION ON STUDENT LEARNING ACTIVITY AND PERFORMANCE ON TWO-VARIABLE LINEAR EQUATIONS - Nurjannah; Laili Habibah Pasaribu; Sakinah Ubudiyah Siregar (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to determine whether there is an effect of YouTube on student learning activeness and performance in class VIII MTS Tarbiyah Islamiyah Ulumahuam students. This activity was carried out offline. The research subjects were MTS Tarbiyah Islamiyah Ulumahuam students and the sample used amounted to 50 students where 25 participants for the experimental class and 25 participants for the control class. The instrument used is a questionnaire of student activeness and learning performance using YouTube as media and documentation. The analysis techniques used are Normality, Homogeneity, and Hypothesis tests. Based on the results of the research conducted, there is an effect of YouTube on the activeness and performance of student learning with a learning model using YouTube seen from the average value of the questionnaire of student learning activeness and performance, namely with a significant value of 0.000. For hypothesis testing using one-way anova test with significant results of 0.000